2021
DOI: 10.48550/arxiv.2110.11271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analyzing and Improving the Optimization Landscape of Noise-Contrastive Estimation

Abstract: Noise-contrastive estimation (NCE) is a statistically consistent method for learning unnormalized probabilistic models. It has been empirically observed that the choice of the noise distribution is crucial for NCE's performance. However, such observations have never been made formal or quantitative. In fact, it is not even clear whether the difficulties arising from a poorly chosen noise distribution are statistical or algorithmic in nature. In this work, we formally pinpoint reasons for NCE's poor performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The exponential loss is, like the logistic loss, a Bregman divergence that was shown to provide a large family of loss functions for the contrastive learning of energy-based models (Gutmann and Hirayama 2011). The result by Liu et al (2021) highlights that for some models, particular instances of the family of loss functions are more suitable than others.…”
Section: Reference Datamentioning
confidence: 95%
See 1 more Smart Citation
“…The exponential loss is, like the logistic loss, a Bregman divergence that was shown to provide a large family of loss functions for the contrastive learning of energy-based models (Gutmann and Hirayama 2011). The result by Liu et al (2021) highlights that for some models, particular instances of the family of loss functions are more suitable than others.…”
Section: Reference Datamentioning
confidence: 95%
“…Telescoping density-ratio estimation by Rhodes et al (2020), Choi et al ( 2021) deals with the density chasm and the flat loss landscape by re-formulating the contrastive problem. A complementary algorithmic approach was taken by Liu et al (2021) who asked whether optimisation techniques can deal with the flat optimisation landscape of the logistic loss when there is a density chasm. They found that, in case of exponential families, normalised gradient descent can deal with the issue.…”
Section: Reference Datamentioning
confidence: 99%